2017
DOI: 10.3389/fonc.2017.00057
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights into Diffuse Intrinsic Pontine Glioma

Abstract: Diffuse intrinsic pontine glioma (DIPG) is a highly aggressive pediatric brainstem tumor with a peak incidence in middle childhood and a median survival of less than 1 year. The dismal prognosis associated with DIPG has been exacerbated by the failure of over 250 clinical trials to meaningfully improve survival compared with radiotherapy, the current standard of care. The traditional practice to not biopsy DIPG led to a scarcity in available tissue samples for laboratory analysis that till recently hindered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 66 publications
(142 reference statements)
4
55
0
Order By: Relevance
“…We identified that approximately 80% of tumors had H3F3A or HIST1H3B mutation. This rate is consistent with previous studies (25). No HIST1H3C mutation was found, likely reflecting its rarity (27).…”
Section: Characterization Of Diffuse Midline Gliomas H3k27m-mutantsupporting
confidence: 93%
See 3 more Smart Citations
“…We identified that approximately 80% of tumors had H3F3A or HIST1H3B mutation. This rate is consistent with previous studies (25). No HIST1H3C mutation was found, likely reflecting its rarity (27).…”
Section: Characterization Of Diffuse Midline Gliomas H3k27m-mutantsupporting
confidence: 93%
“…The median overall survival of patients with H3K27M-mutant tumors was 7.95 months, which is in line with previous studies (23). As expected, within histone mutant tumors, p53 pathway alteration was the most frequent finding (65.71%), followed by PIK3CA/PIK3R1 mutations (14.29%) (25,29). ACVR1 mutations were identified in 11.76% of H3K27Mmutant tumors.…”
Section: Characterization Of Diffuse Midline Gliomas H3k27m-mutantsupporting
confidence: 90%
See 2 more Smart Citations
“…
Pediatric brain tumors account for approximately 25% of all cancers in children and are currently the leading cause of cancer-related deaths in the pediatric population with an estimated incidence of 5.14 cases per 100,000 person years [1]. Up to 10-15% of all pediatric brain tumors arise in the brainstem, with the majority of these classified as the diffuse intrinsic pontine glioma (DIPG) subtype [2].
…”
mentioning
confidence: 99%